Isolation and Identification of Phenolic Compounds from Sea Grape (Coccoloba uvifera (L.) L) - Pasaribu, Albert; Lena, Wirda (Journal of Chemical Natural Resources, 2023)
Isolation and identification of phenolic compounds from Sea Grapes (Coccoloba uvifera (L.) L.) leave, where as much as 1700 g have been macerated using methanol. The concentrated methanol extract was dissolved in water and partitioned with ethyl acetate. Ethyl acetate concentrated extract was separated by column chromatography with chloroform as eluents: methanol 90:10; 80:20; 70:30; 60:40 v/v. The compound obtained was purified by column again using chloroform: ethyl acetate 70:30 v/v with the resulting was 10 mg of brownish yellow paste with a value of Rf = 0.5. The resulting compounds were then analyzed using a UV-Vis, FT-IR, and 1H-NMR spectrophotometer. Based on the data analysis, the results showed phenolic compounds in Sea Grape.